Implementation Of Erp Warehousing Concept In Bare Core Company With Using Odoo 10 (pt. Albasia Nusa Karya) - Rd. Panji Erdinanda Pandu Jiwatama; Rd. Rohmat Saedudin; Umar Yunan (eProceedings of Engineering, 2018)
PT. Albasia Nusa Karya is a newcomer company engaged in the Bare Core industry. The company was established since 2014 at Jalan Pasopati KM 6.2 Leuwigoong, Leles, Garut, Indonesia. As a new company in Bare Core industry, PT. Albasia Nusa Karya still needs a lot of improvements in their companies, especially the challenge to create an optimal business process, accurate, and efficient. Not yet integrated enterprise record process, causing the existence of several potential data management errors. For example, business processes that take place today often produce documents that are not appropriate between the data contained in the procurement and accounting sections. Likewise, in the procurement process is often the difference between the recording of goods requested goods, goods ordered, and with goods received so that data errors occur in the procurement and warehouse. In addition, data redundancies, data duplication, and payment processes tend to be slow Responding to the above problem, sourced from the existing state of business and business process of Odoo 10 Inventory Module, the researcher will create solution for this company to get optimal, accurate, and efficient business process, hereinafter referred as proposal business process. The business process of this proposal will be further installation, configuration, and customization and well packaged in the form of an ERP software that will replace the Odoo 10 business process that has been running for this. With the implementation of ERP system in this company mainly on the inventory and warehousing, all activities related to warehouse and inventory of the company become more structured. Integration of each division is considered to solve the problem that has been there in PT. Albasia Nusa Karya. The suitability of documents, reporting, and business processes of this company will become more secure. Keywords: ERP, Odoo 10, Inventory, Warehousing, Bare, Core